Impact of lymph node dissection in radical cystectomy for bladder cancer: How many vs how far?. (September 2019) - Choi, Se Young; You, Dalsan; Hong, Bumsik; Hong, Jun Hyuk; Ahn, Hanjong; Kim, Choung-Soo
Abstract: Purpose: To determine whether the extent or number of lymph nodes (LNs) is important in muscle-invasive bladder cancer and high-risk non-muscle-invasive bladder cancer patients' oncologic outcomes. Methods: A total of 448 patients who underwent radical cystectomy with lymphadenectomy of standard, extended, and super-extended template were included. Exclusion criteria were neoadjuvant chemotherapy and limited lymphadenectomy. Disease-free survival (DFS) including local recurrence and distant metastasis, cancer-specific survival (CSS), and overall survival (OS) were estimated using the Kaplan-Meier method. Cox hazard regression was applied to analyze risk factors. Results: Standard (n = 124), extended (n = 216), and super-extended group (n = 108) did not show significant differences in the estimated 5-year DFS, CSS and OS rates. On multivariate analysis, the number of removed LNs was a significant factor for distant metastasis-free (hazard ratio [HR] 0.981, p = 0.0222), CSS (HR 0.980, p = 0.0021) and OS (HR 0.984, p = 0.0032). However, the template was not significant in distant metastasis-free survival, CSS and OS. On Kaplan-Meier curve, the number of removed LN showed significant differences in DFS, CSS, and OS. In the subgroup of positive LNs, number of removed LNs was associated with favorable DFS (HR = 0.969, p = 0.0115), CSS (HR = 0.967, p = 0.0068) and OS (HR = 0.971, p = 0.0028). Conclusion: The number of removed LNs was a more important factor for CSS and OS than the extent of lymphadenectomy. Meticulous and extended LN dissection can be helpful in controlling recurrence, and its survival benefit might be maximized in cases with positive LN. Meanwhile, the survival benefit of super-extended lymphadenectomy was limited for this patient population. Highlights: The number of removed lymph nodes was a more important factor for oncologic outcomes than the extent of lymphadenectomy. Meticulous & extended lymph node dissection can help to control local recurrence, especially in positive lymph node cases. The survival benefit of super-extended lymphadenectomy was limited.